Réponses

2012-09-23T11:45:32+02:00

– 2 x + 9 = 5 x – 5 => -2x+9-5x+5=0

-7x+14=0

-7x=-14

x=-14/-7=2

 

5 x – 4 =  – 3 x + 10=> 

5x-4+3x+10=0

8x+6=0

x=6/8=3/4

2012-09-23T11:47:34+02:00

Pour la première: -2x+9=5x-5

                          -2x-5x= -5 -9

                          -7x=-14

                           x= -14/-7

                           x=2

 

Pour la deuxième: 5x-4=-3x+10

                            5x+3x=10+4

                            8x=14

                            x= 14/8

                            x= 1,75